A cross‐sectional exploration of the personality traits of dietitians. Issue 5 (19th August 2014) - Ball, L.; Eley, D. S.; Desbrow, B.; Lee, P.; Ferguson, M.
Abstract: Background: Personality traits refer to habitual patterns of behaviour, thought and emotions, and have been shown to influence health professionals' career decisions, career development, job satisfaction and retention. There is an opportunity to better understand and support the career pathways of dietitians by exploring their personality traits. The two primary aspects of personality are: (i) temperament traits, which determine automatic emotional responses to experiences, and are generally stable over lifetime, and (ii) character traits, which reflect personal goals and values, and tend to develop with life experience. The present study explored the levels of temperament and character traits of dietitians, as well as their relationship to demographic variables. Methods: The study comprised a cross‐sectional online survey of 346 Australian dietitians [95% female; mean (SD) age 32 (10) years; mean (SD) time since graduation 7 (9) years]. Temperament and character traits were measured by the Temperament and Character Inventory. Key demographic variables were measured to describe career decisions and pathways of dietitians. Multivariate analyses of variance was used to investigate the relationship between demographic variables and personality traits. Results: Levels of several traits were significantly associated with gender, age and highest level of education. In comparison to the general population, the dietitians displayed average levels of Novelty Seeking; high levels of Harm Avoidance, Reward Dependence, Persistence, Self‐Directedness and Cooperativeness; and low levels of Self‐Transcendence. Conclusions: The dietitians in the present study displayed levels of personality traits that were similar to other health professionals, although they differed from the general population. These findings are the precursor to further work that may inform recruitment strategies and career counselling in dietetics.